2019
DOI: 10.1155/2019/2981796
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nanoparticle-Stacked 1,1-Diamino-2,2-Dinitroethylene (FOX-7) Microspheres with Increased Thermal Stability

Abstract: Nanoparticle-stacked 1,1-diamino-2,2-dinitroethylene (FOX-7) microspheres were successfully prepared by spray-drying, and rod-shaped FOX-7 was obtained by the solvent/nonsolvent method for comparison. The microstructure features of samples were characterized using scanning electron microscopy (SEM) and powder X-ray diffraction (XRD), and the thermal properties were also investigated by differential scanning calorimetry (DSC). From the SEM analysis, the particle size of the rod-shaped FOX-7 is about 10 μm, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Spray-drying can easily control the composition and particle size of a product. It has been extensively used in the preparation of energetic materials [15][16][17]. For instance, a kind of aluminum/HMX nanocomposite was prepared by Zhigach et al [18] successfully with the spray-drying method, with the distribution of the components uniform.…”
Section: Introductionmentioning
confidence: 99%
“…Spray-drying can easily control the composition and particle size of a product. It has been extensively used in the preparation of energetic materials [15][16][17]. For instance, a kind of aluminum/HMX nanocomposite was prepared by Zhigach et al [18] successfully with the spray-drying method, with the distribution of the components uniform.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 6 , three different samples had a similar exothermic decomposition process, which indicated that solid-phase decomposition kinetics dominated their thermal decomposition process. The DSC curves showed the first endothermic peak for the β → γ phase transition [ 21 ] and the second endothermic peak for the γ → δ transition [ 22 ]. After the phase transitions, there were two successive exothermic decomposition processes of FOX-7: the first with the peak at ca.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity of nano-spherical FOX-7 particles is reduced, and the thermal stability is improved as compared to raw FOX-7. Yuanping Zhang et al 8 used spray-drying method to prepare nanoparticle-stacked FOX-7 microspheres. The particle size of the microspheres FOX-7 formed by stacking nanoparticles (100–250 nm) is 1–5 μm, which is significantly smaller than the raw FOX-7.…”
Section: Introductionmentioning
confidence: 99%